2022
DOI: 10.52970/grmapb.v3i1.206
|View full text |Cite
|
Sign up to set email alerts
|

Business Strategy Approach to Informal Small Businesses in Increasing Productivity and Competitiveness

Abstract: The aim of this study is to analyze (1) performance on production capabilities, (2) Market orientation on performance, (3) innovative performance, (4) Performance on work productivity, (5) Production capacity on competitiveness, (6) Market orientation on competitiveness (7) Innovative on competitiveness (8) Work productivity on competitiveness (9) Performance on competitiveness. The research used primary data by surveying as many as 187 Informal small business respondents in Surabaya city as samples. Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Prior studies indicated that firms can perform better if their production costs are reduced, and, consequently, the profit margin is higher. Eco-efficiency actions can also be implemented in several ways: directly through the use of the latest eco-friendly technologies and indirectly by applying proactive environmental strategies within their business model [34]. Nevertheless, implementing resource efficiency actions might initially increase production costs [35].…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…Prior studies indicated that firms can perform better if their production costs are reduced, and, consequently, the profit margin is higher. Eco-efficiency actions can also be implemented in several ways: directly through the use of the latest eco-friendly technologies and indirectly by applying proactive environmental strategies within their business model [34]. Nevertheless, implementing resource efficiency actions might initially increase production costs [35].…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…Diferentemente do que se vê na sociedade contemporânea, onde a produtividade é um fator essencial para a lucratividade dos negócios (Mansur;Djaelani, 2023), a execução da manutenção preventiva não tinha tanta importância, uma vez que a sua feitura consistia tão somente na troca da peça defeituosa (Correa;Camargo, 2022).…”
Section: A Manutenção Corretivaunclassified